Agricultural Communications Efforts During Florida’s Medfly Infestations of 1997 and 1998 - Ricky Telg; Mary Gail Dufresne (Journal of Applied Communications, 2001)
This case study examined the communications methods and results of Florida’s agricultural communicators during the Mediterranean fruit fly infestations of 1997 and 1998. Eight agricultural communicators actively participating in the communications efforts during the infestations were interviewed. Findings included the following: activist groups were able to “strike first” and control the media messages for a period of time that was damaging to the agricultural industry’s efforts of spraying malathion, the agricultural community often discounted activists as extremists whose arguments were invalid and without merit, and personal relationships and personal contacts were essential for the agricultural community to calm the public’s environmental and health fears.